Nutritional and sensory quality of buns enriched with soy fiber (Okara) - Bhavya S.N.; Jamuna Prakash (Journal of Engineering & Processing Management, 2018)
Dietary fiber obtained from by-products of food industries acts as a potential functional food ingredient and used in baking, beverages and meat products. Soybean, a rich source of plant protein is a suitable substitute to dairy milk. Processing of soy milk leaves behind large quantities of fiber, which could be incorporated in food formulation as a dietary supplement. With this background high fiber buns were formulated using soy fiber at different levels and analyzed for nutritional quality, physical characteristic and sensory acceptability. Nutritional characteristics of enriched buns were determined using standard methods and results (per 100 g) were: protein, 7.1-7.7 g; fat, 4.8-6.6 g; iron 2.2-3.0 mg and calcium, 74.0-81.0 mg. Phytic acid and tannin were in the range of 19.0-22.8 mg and 47.4-50.1 mg/100g respectively. Bioaccessible Fe ranged from 11.1-23.3 % and Ca from 50.2-95.5 % of total. In vitro digestible protein and starch ranged from 46.8-49.5 and 34.9-68.6 % of total respectively. Addition of fiber influenced the color of the buns as measured by Hunter Lab color meter. Incorporation of soy fiber lowered sensory scores of buns. In conclusion, soy fiber buns were nutritionally superior and can fulfill the consumer requirement of health food.
Keywords: fiber enrichment; nutritional composition; digestible protein and starch; bioaccessible iron and calcium; sensory quality